Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s12870-021-03147-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiles revealed molecular mechanisms of alternating temperatures in breaking the epicotyl morphophysiological dormancy of Polygonatum sibiricum seeds

Abstract: Background To adapt seasonal climate changes under natural environments, Polygonatum sibiricum seeds have a long period of epicotyl morphophysiological dormancy, which limits their wide-utilization in the large-scale plant progeny propagation. It has been proven that the controlled consecutive warm and cold temperature treatments can effectively break and shorten this seed dormancy status to promote its successful underdeveloped embryo growth, radicle emergence and shoot emergence. To uncover t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
3
9
0
Order By: Relevance
“…When the germination rate reached 60% (30 days), it was sluggish and had a tendency to be more consistent ( Figure 1A ). After that, the seeds stopped growing and entered epicotyl dormancy ( Liao et al, 2021 ). This study found, to release the epicotyl dormancy of P. cyrtonema seeds, the application of a certain concentration of 6-BA could significantly increase the emergence rate then relieved the dormancy of seeds ( Figure 1B ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…When the germination rate reached 60% (30 days), it was sluggish and had a tendency to be more consistent ( Figure 1A ). After that, the seeds stopped growing and entered epicotyl dormancy ( Liao et al, 2021 ). This study found, to release the epicotyl dormancy of P. cyrtonema seeds, the application of a certain concentration of 6-BA could significantly increase the emergence rate then relieved the dormancy of seeds ( Figure 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…P. cyrtonema seeds began to enter the epicotyl dormancy after the bulb appeared. The dormancy state can be broken effectively by alternating temperatures ( Liao et al, 2021 ). However, other studies have shown that exogenous phytohormones can also relieve dormancy ( Yang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PacBio single molecular real time (SMRT) sequencing can avoid assembly errors and provide complete transcript sequence information for species in case of no or poor reference genomes ( Workman et al, 2018 ). To obtain the full-length transcript information of plants and accurately address biological problems, a method combining PacBio SMRT sequencing with Illumina sequencing has been used in several studies: for example, to determine how alternating temperature breaks the morphophysiological dormancy of Polygonatum sibiricum seeds ( Liao et al, 2021 ), response to drought stress during seed germination of Adzilla beans ( Zhu et al, 2020 ), and potential transcriptional variants of genes involved in oil biosynthesis in Camellia oleifera seeds ( Gong et al, 2020 ). Similar to that in previous studies, this combined method can be used to study C. rigescens seed germination and will provide useful genetic information as well as allow elucidation of germination mechanisms.…”
Section: Introductionmentioning
confidence: 99%